Cake Breaker Conveyor Machine Maintenance System Analysis Using the Reliability-Centered Maintenance (RCM) Method - Basuki Nanda; Valentino Roni (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2023)
Machine maintenance plays a vital role in the production activities of a company, which concerns the smooth and bottleneck of production. This research was conducted in a company engaged in palm oil processing. The company often suffers from machine breakdowns and has not found a suitable solution. Reliability Maintenance is one of the methods used to determine the appropriate maintenance actions for each critical component on the Cake Breaker Conveyor (CBC) machine, based on analysis using Failure Mode and Effect Analysis (FMEA) by looking at the highest RPN value of each component, 4 critical elements are obtained from the 11 main features of the Cake Breaker Conveyor (CBC) machine, namely bearing parts, Universal Joint, Rod Clutch and Pen. Determine the maintenance schedule of critical components at the seed separation station. Taking damage, lognormal distribution, proposed replacement schedule 461.5 (hours), pen damage, normal distribution, proposed replacement schedule 587.29 (hours), universal joint damage, normal distribution, proposed replacement schedule 536.46 (hours), clutch rod damage, normal distribution, proposed replacement schedule 581.6 (hours), and axle damage, normal distribution, proposed replacement schedule 586.6 (hours).